2020
DOI: 10.14715/cmb/2020.66.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to bacterial infection, complication occurring after cardiac surgery

Abstract: To analyze the occurrence of resistant bacterial infection in patients undergoing cardiac surgery hospitalized in the surgical specialty hospital, in Erbil city, Iraq. A prospective study was done on a total of 138 patients operated and hospitalized in an intensive care unit and surgical wards. Bacterial isolates identification was done according to cultural characteristics, microscopic examination, some biochemical tests, analytic Profile Index 20E& API Staph, confirmed with VITEK® 2 compact system (BioMé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, the degree of resistance is not specified and there may be a difference between a microbe that is resistant to a single agent compared to one that is multidrug-resistant, which could both be classified as antimicrobial resistance. This may be important as a prospective study of 138 patients who underwent cardiac surgery found that multidrug-resistant bacterial isolates were widespread and there are increasingly emerging strains of extended-spectrum beta-lactamases-producing Gram-negative bacteria Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli, especially, among patients with prolonged admission to intensive care units [20]. The studies of multidrug resistance have been evaluated in other types of patient cohorts [21][22][23].…”
Section: Key Considerations Regarding the Findingsmentioning
confidence: 99%
“…Furthermore, the degree of resistance is not specified and there may be a difference between a microbe that is resistant to a single agent compared to one that is multidrug-resistant, which could both be classified as antimicrobial resistance. This may be important as a prospective study of 138 patients who underwent cardiac surgery found that multidrug-resistant bacterial isolates were widespread and there are increasingly emerging strains of extended-spectrum beta-lactamases-producing Gram-negative bacteria Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli, especially, among patients with prolonged admission to intensive care units [20]. The studies of multidrug resistance have been evaluated in other types of patient cohorts [21][22][23].…”
Section: Key Considerations Regarding the Findingsmentioning
confidence: 99%